Workability and compressive strength of ductile self compacting concrete (DSCC) with various cement replacement materials - Nuruddin, M.F. (2014)
Ductile self compacting concrete (DSCC) is one of the advanced materials which combines self compacting abilities and ductility to address the current industry problems. A study on DSCC with various cement replacement materials was conducted. Up to 20 of cement in DSCC was replaced by Microwave Incinerated Rice Husk Ash (MIRHA), silica fume (SF) and fly ash (FA) in certain ratios. The experiments of self compacting ability such as V-funnel test, slump flow and L-box test were conducted in order to ensure the DSCC with various cement replacement materials fulfilled the requirements for self compacting. Besides that, comparison of compressive strength is made between the control DSCC and DSCC with various cement replacement materials. The results show that DSCC with replacement of 10 FA and 10 MIRHA achieved the highest compressive strength without scarifying the self compacting abilities. Â© 2014 Elsevier Ltd. All rights reserved.